Cobalt-free steel, preparation methods and applications

By carefully setting the proportion of elements and structural combinations in the steel, a martensite and austenite biphasic structure is formed, combining cold rolling and liquid nitrogen deep-cold treatment, the traditional steels have solved the tensile strength, yield strength and fracture toughness. It has achieved efficient and low-cost steel performance improvement, meeting the high requirements in the aerospace field.

CN116065101BActive Publication Date: 2025-01-10CHINA NUCLEAR POWER TECH RES INST CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211729450.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-01-10
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

Traditional ultra-high strength steels have limitations in taking into account tensile strength, yield strength, fracture toughness and plasticity, and are costly, and the austenite transformation is not completely likely to cause material fatigue failure, making it difficult to meet the performance of steel in the fields of aerospace and other fields. High demand.

Method used

By carefully setting the ratio of elements such as Al, Ni, Cr and Mo, a cobalt-free steel is developed, using a martensite and austenite biphasic structure, including a co-niAl phase and a semi-common carbide phase, combined with cold Rolling and liquid nitrogen deep-cooling treatment form stable austenite and martensite, improving the mechanical properties of the steel.

Benefits of technology

The tensile strength and elongation rate of cobalt-free steel have been improved, the comprehensive mechanical properties of the material have been significantly improved, the cost has been reduced, and the requirements for service safety of steel in the fields of aerospace and other fields have been met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116065101B_ABST
    Figure CN116065101B_ABST
Patent Text Reader

Abstract

The present application relates to a cobalt-free steel and its preparation method and application, which contains, by mass percentage: 1% to 10% Cr, 5% to 17% Ni, 0.5% to 5% Al, 0.25% to 2% Mo, 0% to 2% Mn, 0% to 0.2% Nb, 0.01% to 0.2% C, and the balance Fe. The cobalt-free steel can obtain a super-strong steel with stable residual austenite and excellent comprehensive mechanical properties without adding Co, Ti, B, etc. The tensile strength of the cobalt-free steel is ≥1900MPa, and the elongation after fracture is ≥10%, which can meet the service safety requirements of steel in special application environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of steel materials, and in particular to a cobalt-free steel and a preparation method and application thereof. Background Art

[0002] Ultra-high-strength steel generally refers to steel with a strength higher than 1500MPa, which is widely used in aircraft landing gear, rocket engine casings, high-pressure vessels, high-strength bolts and other fields. Most traditional ultra-high-strength steels use a single high-strength martensite or bainite as the matrix, and the aged steel is prepared by strengthening the precipitation of a single type of precipitate phase through aging. Although it is often difficult for a single steel material to take into account multiple mechanical properties, which limits the further improvement of the material's strength and plasticity, incomplete austenite transformation often easily causes material fatigue failure. Therefore, most ultra-high-strength steels are still martensitic aging steels. In addition, traditional technologies also strengthen martensitic properties by introducing Co, Ti, etc.

[0003] With the advancement of technology and the deepening of application fields, important fields such as aerospace, transportation, advanced energy, and national defense construction have put forward higher requirements for the performance of steel. Not only high yield strength is required, but also excellent fracture toughness, plasticity, fatigue strength, corrosion resistance and even low raw material and process costs are required to ensure service safety and energy security. Therefore, it is of great significance to develop steel with tensile strength, yield strength, fracture toughness and low cost. Summary of the invention

[0004] Based on this, the objectives of this application include providing a cobalt-free steel, avoiding the addition of Co and obtaining steel with excellent mechanical properties by carefully setting the ratios of elements such as Al, Ni, Cr and Mo, and also providing a method for preparing cobalt-free steel and the application of cobalt-free steel.

[0005] In a first aspect of the present application, a cobalt-free steel is provided, comprising, by mass percentage, 1% to 10% Cr, 5% to 17% Ni, 0.5% to 5% Al, 0.25% to 2% Mo, 0% to 2% Mn, 0% to 0.2% Nb, 0.01% to 0.2% C, and the balance Fe.

[0006] In some embodiments, the cobalt-free steel has two phase structures of martensite and austenite, and contains, by mass percentage, 1% to 10% Cr, 5% to 17% Ni, 0.5% to 5% Al, 0.25% to 2% Mo, 0% to 2% Mn, 0% to 0.2% Nb, 0.01% to 0.2% C, and the balance Fe.

[0007] In some embodiments, the cobalt-free steel comprises a martensitic matrix, and a coherent NiAl phase and a semi-coherent carbide phase dispersed in the martensitic matrix, wherein the semi-coherent carbide phase may be selected from (Mo, Cr) 2 C phase, Cr 2 One or more of C phase, NbC phase.

[0008] In some embodiments, the cobalt-free steel satisfies at least one of the following characteristics:

[0009] The coherent NiAl phase has a B2 type structure;

[0010] The equivalent radius of the coherent NiAl phase is 0.5 to 4 nm;

[0011] The volume ratio of the coherent NiAl phase in the cobalt-free steel is 4% to 10%;

[0012] The number density of the coherent NiAl phase in the cobalt-free steel is 2×10 24 / m 3 ~5×10 24 / m 3 ;

[0013] Mn is distributed at one end of at least a portion of the coherent NiAl phase.

[0014] In some embodiments, the cobalt-free steel, when the semi-coherent carbide phase comprises (Mo, Cr) 2 Phase C meets at least one of the following characteristics:

[0015] The semi-coherent (Mo, Cr) 2 Phase C has an HCP-type structure;

[0016] The semi-coherent (Mo,Cr) 2 The equivalent radius of the C phase is 0.1 to 2.5 nm;

[0017] At least a portion of the semi-coherent (Mo, Cr) 2 The deviation of the major axis of the C phase relative to the {100} crystal plane direction of the martensitic matrix does not exceed 2°;

[0018] The semi-coherent (Mo,Cr) 2 The number density of C phase in the cobalt-free steel is 4.5×10 23 / m 3 ~5.5×10 23 / m 23 ;

[0019] The coherent NiAl phase and the semi-coherent (Mo, Cr) 2The number density ratio of phase C is (6.5~7.5):1.

[0020] In some embodiments, in the cobalt-free steel, the martensitic matrix includes nano-twinned martensite; the nano-twinned martensite is in the shape of long strips, and the average width is 14 to 15 nm.

[0021] In some embodiments, the cobalt-free steel satisfies at least one of the following characteristics:

[0022] In the cobalt-free steel having a dual phase of martensite and austenite, the volume ratio of the martensite to the austenite is (7-20):1;

[0023] The volume ratio of the austenite in the cobalt-free steel having a martensite-austenite dual phase is selected from 11% to 13%;

[0024] The austenite includes particles of 1 to 2 μm;

[0025] The austenite is distributed at the high-angle grain boundaries of the martensite, and the high-angle grain boundaries refer to grain boundaries where the orientation difference between adjacent grains is greater than 15°.

[0026] In some embodiments, the cobalt-free steel satisfies at least one of the following characteristics:

[0027] In the cobalt-free steel, the total weight proportion of Ni element and Al element is 8.5% to 22%;

[0028] In the cobalt-free steel, the weight ratio of Ni element to Al element is (3-9):1.

[0029] In some embodiments, the cobalt-free steel satisfies at least one of the following characteristics:

[0030] In the cobalt-free steel, the total weight proportion of Mo element and Cr element is 2% to 7%;

[0031] In the cobalt-free steel, the weight ratio of Mo element to Cr element is (0.05-1.5):1.

[0032] In some embodiments, the cobalt-free steel comprises, by mass percentage, 2.5% to 9% Cr, 12% to 14% Ni, 1% to 3% Al, 1% to 1.5% Mo, 0% to 1.5% Mn, 0% to 0.1% Nb, 0.08% to 0.2% C, and the remainder Fe and unavoidable impurities.

[0033] A second aspect of the present application provides a method for preparing cobalt-free steel, comprising the following steps:

[0034] The raw materials are smelted to form ingots; wherein the raw materials are mixed according to the element ratio of the cobalt-free steel described in the first aspect;

[0035] The ingot is homogenized at 1150-1250° C. and water-cooled to 20-35° C.;

[0036] cold rolling the homogenized and water-cooled ingot to obtain a cold-rolled material;

[0037] The cold-rolled material is subjected to a solution treatment at 900-1000° C., water-cooled to 20-35° C., and deep-cooled with liquid nitrogen to obtain a steel material having martensite and austenite;

[0038] The steel material having martensite and austenite is subjected to aging treatment at 500-600° C. to obtain the cobalt-free steel.

[0039] In some embodiments, the preparation method satisfies at least one of the following characteristics:

[0040] The ingot is homogenized at 1150-1250° C. for 1-3 hours;

[0041] The total reduction of the cold-rolled material obtained by cold rolling is 30% to 70%;

[0042] The cold-rolled material is subjected to a solid solution treatment at 900-1000° C., and water-cooled to 20-35° C. to obtain supersaturated martensite; the supersaturated martensite is subjected to liquid nitrogen deep cooling to eliminate unstable austenite, and the steel having martensite and austenite is obtained; the cold-rolled material is subjected to a solid solution treatment at 900-1000° C. for 5-60 minutes;

[0043] The steel material having martensite and austenite is subjected to aging treatment at 500-600° C. for 60-720 minutes.

[0044] A third aspect of the present application provides a stainless steel product, which is made of the cobalt-free steel described in the first aspect or the cobalt-free steel prepared by the preparation method described in the second aspect.

[0045] The fourth aspect of the present application provides a cobalt-free steel as described in the first aspect or a cobalt-free steel prepared by the preparation method as described in the second aspect as an ultra-high-strength steel, or in the preparation of aircraft landing gear, rocket engine casing, high-strength bolts for high-pressure vessels or applications.

[0046] The present application provides a cobalt-free steel, which can obtain a steel with a higher tensile strength (e.g., ≥1900Mpa) and a higher elongation after fracture (e.g., ≥10%) without adding Co, Ti, etc. The steel has excellent comprehensive mechanical properties, and the mechanical performance parameters such as tensile strength, yield strength, elongation at fracture, uniform elongation and plasticity can meet the service safety requirements of steel in special application environments.

[0047] In the preparation method of cobalt-free steel provided in the present application, the raw materials are first vacuum melted to make the microscopic components uniform, then the ingot is homogenized, water-cooled to room temperature and then cold-rolled to obtain a steel plate, then the steel plate is solution treated and water-cooled and liquid nitrogen deep-cooled to eliminate unstable austenite, and finally aging is performed at an appropriate temperature to obtain cobalt-free steel. The preparation method is relatively simple and easy to mass-produce, and the obtained steel has good plasticity and work hardening ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0049] Figure 1 , (a), (b), and (c) are the engineering stress-strain curve, true stress-strain and work hardening rate curve of the steel in Example 1, respectively, compared with the tensile strength (UTS), yield strength (YS), total elongation (TE), and uniform elongation (UE) of traditional ultra-high strength steel Aermet100 and MaragingC300.

[0050] Figure 2 , (a) and (b) are the overall and local magnifications of the fracture surface of the test steel tensile specimen, respectively.

[0051] Figure 3 , Example 1 EBSD phase distribution.

[0052] Figure 4 , (a), (b) and (c) are the low-magnification TEM, high-magnification TEM and diffraction spots (SAED) of twinned martensite, respectively.

[0053] Figure 5 , (a)~(c) are the dark field images, high resolution (HRTEM) and FFT images of NiAl phase, respectively, and (d)~(f) are the dark field images, high resolution (HRTEM) and FFT images of M2C phase, respectively.

[0054] Figure 6, (a), (b) and (c) are the isoconcentration surface distributions of 30at.% NiAl and 10at.% CrMoC, the isoconcentration surface distributions of 30at.% NiAl and 4at.% Mn with a thickness of 3nm, and the isoconcentration surface distributions of 30at.% NiAl and 10at.% CrMoC with a thickness of 3nm, respectively. (d) and (e) are the size distribution diagrams of NiAl phase and M2C phase, respectively.

[0055] Figure 7 , (a) and (b) are the composition distribution diagrams of all isoconcentration surfaces of 30at.%NiAl and 10at.%CrMoC, respectively.

[0056] Figure 8 , engineering stress-strain curve of Example 2.

[0057] Fig. 9 , engineering stress-strain curve of Example 3.

[0058] Fig.10 , engineering stress-strain curve of comparative example 1.

[0059] Fig.11 , engineering stress-strain curve of comparative example 2.

[0060] Fig.12 , a method for preparing cobalt-free steel in one embodiment of the present application. DETAILED DESCRIPTION

[0061] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0062] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0063] the term

[0064] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0065] In the present application, "plurality", "multiple", "multiple times", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0066] Herein, "preferred", "better", "more preferred", and "suitable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of this application. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0067] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0068] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0069] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0070] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0071] In the present application, the term "room temperature" generally refers to 4°C to 35°C, preferably 20°C±5°C. In some embodiments of the present application, room temperature refers to 20°C to 30°C.

[0072] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3-5h means that the units of the left endpoint "3" and the right endpoint "5" are both h (hours).

[0073] Tensile strength: Tensile strength is a symbol that represents the material's maximum resistance to plastic deformation and is the maximum engineering stress reached in a tensile test.

[0074] Yield strength: Yield strength is the yield limit of metal materials when they yield, that is, the stress that resists slight plastic deformation. For metal materials without obvious yield phenomenon, the stress value that produces 0.2% residual deformation is specified as its yield limit, which is called conditional yield limit or yield strength.

[0075] Uniform elongation: the elongation from the beginning of deformation to the occurrence of necking, including elastic and plastic deformation parts.

[0076] Elongation at break: also known as elongation after fracture, refers to the percentage of the elongated length of the test rod to its original length when the metal material breaks under the action of external force (tensile force).

[0077] Yield ratio: The yield ratio refers to the ratio of the yield point (yield strength) of a material to its tensile strength.

[0078] Impurity content of steel: Steel generally includes unavoidable impurities. According to weight percentage, the impurity content is generally: S≤10ppm, P≤15ppm, O≤10ppm, N≤10ppm, and the total impurity content is ≤50ppm.

[0079] Homogenization treatment: also called homogenization treatment. A means to improve the metallurgical quality and extrusion performance of the ingot. Generally, heat treatment is carried out at a temperature higher than the intermediate annealing temperature of the alloy to improve the internal crystal structure of the alloy and eliminate casting stress, that is, it can change the internal structure and performance of the continuous casting billet, which is beneficial to the subsequent stretching production.

[0080] Cold rolling: hot-rolled steel coils are used as raw materials, and after pickling to remove the oxide scale, cold rolling is carried out. The finished product is a hard rolled coil. Due to the cold work hardening caused by continuous cold deformation, the strength and hardness of the hard rolled coil increase, and the toughness and plasticity index decrease. Therefore, the stamping performance will deteriorate and it can only be used for parts with simple deformation.

[0081] Solution treatment: also known as solid solution strengthening. First, carbon solid solution strengthens martensite. The supersaturated interstitial carbon causes square distortion of the lattice in the a-phase lattice, forming a strong stress field. This stress field has a strong exchange effect with dislocations, hindering the movement of dislocations and thus increasing the hardness and strength of martensite.

[0082] Liquid nitrogen cryogenic treatment: refers to the method of using liquid nitrogen as a refrigerant to treat the workpiece at a temperature below -130°C.

[0083] Aging treatment: refers to the heat treatment process in which the alloy workpiece is placed at a higher temperature or room temperature after solution treatment, cold plastic deformation or casting, forging, and its performance, shape and size change over time.

[0084] One of the mainstream ideas for improving the mechanical properties of steel in traditional technology is to improve the preparation method to maximize the transformation of austenite to martensite, reduce the content of austenite involved in obtaining martensitic aging steel; the second mainstream idea is to obtain martensitic strengthening phase by adjusting the type and proportion of alloys, such as introducing a large amount of Co, Ni, Mo and rare earth metals to achieve precipitation strengthening phase, or introducing elements such as Ti, P and B that can significantly improve tensile properties. However, steel containing a large amount of Co, Ni, Mo and rare earth elements is expensive, and although elements such as Ti, P and B are beneficial to improving grain boundary characteristics and tensile properties, they are unstable at high temperatures, affecting the toughness and plasticity of steel.

[0085] After extensive experimental research and exploration, the inventors of the present application have discovered a cobalt-free steel that can better overcome the above-mentioned problems.

[0086] In a first aspect of the present application, a cobalt-free steel is provided, which can obtain a steel material with excellent mechanical properties without adding Co and Ti.

[0087] In a first aspect of the present application, a cobalt-free steel is provided, comprising, by mass percentage, 1% to 10% Cr, 5% to 17% Ni, 0.5% to 5% Al, 0.25% to 2% Mo, 0% to 2% Mn, 0% to 0.2% Nb, 0.01% to 0.2% C, and the balance Fe.

[0088] In this application, Ni, Al, Cr and Mo elements are selected and the proportion of each element in the raw material is carefully set, and cobalt-free steel with excellent comprehensive mechanical properties is obtained while avoiding the use of high-cost Co, Ti, etc. The precipitation phase precipitates in the specific element ratio in the cobalt-free steel avoid the formation of brittle cementite and significantly improve the strength and plasticity of the material. The cobalt-free steel has excellent mechanical properties such as tensile strength, uniform elongation and plasticity, and can meet the requirements of special application fields such as aerospace, high-pressure vessels, high-end manufacturing and other fields for the service safety of steel.

[0089] In some embodiments, the cobalt-free steel has two phase structures of martensite and austenite, and contains, by mass percentage, 1% to 10% Cr, 5% to 17% Ni, 0.5% to 5% Al, 0.25% to 2% Mo, 0% to 2% Mn, 0% to 0.2% Nb, 0.01% to 0.2% C, and the balance Fe.

[0090] The specific ratio of martensite and austenite and the fine element ratio in the cobalt-free steel with martensite-austenite dual phase make the residual austenite in the steel stable austenite, and the discontinuous austenite is evenly distributed at positions such as the original grain boundaries and lath boundaries, further improving the strain hardening and uniform elongation without significantly reducing the material strength.

[0091] Cr: The most important element that plays a decisive role in the corrosion resistance of stainless steel. Cr is also a strong ferrite forming element, which can reduce the γ phase area and reduce the M s point.

[0092] In some embodiments, the cobalt-free steel contains 1% to 10% Cr in mass percentage, further can be 1% to 9%, further can be 2.5% to 9%, and can also be selected from the following mass percentage or the interval consisting of two mass percentages: 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc.

[0093] The Ni element is an austenite-forming element and an intermetallic compound strengthening element. It can form a B2-NiAl phase that is completely coherent with the BCC matrix when combined with Al. The applicant has found through a large number of experiments that the aforementioned cobalt-free steel has excellent mechanical properties, and it is speculated that this may be because the Ni element is beneficial to the toughness of the material. However, when the Ni content is higher than the appropriate range, the mechanical properties of the steel decrease, and the austenite stability is relatively high, resulting in excessive and unstable residual austenite in the room temperature steel, which will greatly affect the strength of the steel; and when the Ni content is lower than the appropriate range, the Ni content dissolved in the matrix will be lower, resulting in brittle fracture.

[0094] In some embodiments, the cobalt-free steel contains 5% to 17% Ni by mass percentage, and can further be 12% to 17%, and further can be 12% to 14%, and can also be selected from the following one or two mass percentages: 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, etc.

[0095] Al is a strong ferrite-forming element and also a B2 strengthening phase-forming element. The applicant has found through a large number of experiments that when the Al content increases appropriately, the B2 phase precipitation temperature increases, but when the Al content is higher than the appropriate range, the brittleness of the steel increases. It is speculated that this may be because the increase in Al content increases the harmful precipitation phase, causing the steel to undergo brittle fracture.

[0096] In some embodiments, the cobalt-free steel contains 0.5% to 5% Al by mass percentage, and can further be 1% to 5%, and further can be 1% to 3%. It can also be selected from the following mass percentages or an interval consisting of two mass percentages: 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.

[0097] The applicant has found through a large number of experiments that adding an appropriate amount of Mo element can help reduce the lattice constant difference between the ferrite matrix and B2-NiAl, which is beneficial to the solid solution process, and to a certain extent reduces the NiAl nucleation work and inhibits the growth of NiAl. At the same time, it is found that when the Mo-containing carbide precipitation phase is evenly distributed, it is beneficial to improve the strength and toughness of the steel.

[0098] In some embodiments, the cobalt-free steel contains 0.25% to 2% Mo by mass percentage, and can further be 1% to 2%, and further can be 1% to 1.5%. It can also be selected from the following mass percentages or an interval consisting of two mass percentages: 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2%, etc.

[0099] The distribution of Mn has a significant effect on the properties of steel. Mn preferentially occupies the Al sublattice, which is beneficial to the distribution of Mn into NiAl nanoparticles, which not only increases the driving force but also reduces the strain energy of nucleation, thereby significantly reducing the critical energy of NiAl nanoparticle formation in ferritic steel.

[0100] In some embodiments, the cobalt-free steel contains 0% to 2% Mn by mass percentage, and can further be 0% to 1.75%, and further can be 0% to 1.5%, and can also be selected from the following mass percentages or an interval consisting of two mass percentages: 0%, 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2%, etc.

[0101] In some embodiments, the cobalt-free steel contains 0% to 0.2% Nb by mass percentage, further can be 0% to 0.15%, further can be 0% to 0.1%, and can also be selected from the following mass percentage or an interval consisting of two mass percentages: 0%, 0.05%, 0.1%, 0.15%, 0.2%, etc.

[0102] In some embodiments, the cobalt-free steel contains 0.01% to 0.2% C by mass percentage, and can further be 0.05% to 0.2%, and further can be 0.08% to 0.2%. It can also be selected from the following one or two mass percentages: 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, etc.

[0103] In some embodiments, the cobalt-free steel of the first aspect further includes inevitable impurities, and the inevitable impurities include, by mass percentage: S≤0.002, P≤0.002, O≤0.003, N≤0.003, and the total content of the inevitable impurities is ≤0.01. The presence of these impurities will not have an adverse effect on the mechanical properties of the steel.

[0104] The specific ratio of martensite and austenite and the fine element ratio in the cobalt-free steel with martensite-austenite dual phase make the residual austenite in the steel stable austenite, and the discontinuous austenite is evenly distributed at positions such as the original grain boundaries and lath boundaries, further improving the strain hardening and uniform elongation without significantly reducing the material strength.

[0105] Traditional technologies have attempted to strengthen the martensitic aging steel matrix by introducing coherent phases, semi-coherent phases, and incoherent phases, and precipitating single incoherent and semi-coherent precipitates in the supersaturated martensitic matrix. However, the structure of the precipitate phase is difficult to control, and the strengthening effects of different elements and proportions vary greatly. The precipitation phase strengthening method often limits the further improvement of the material's strength and plasticity.

[0106] In some embodiments, the tensile strength of the cobalt-free steel is ≥1800MPa, further ≥1850MPa, further ≥1900MPa, and can also be selected from any one of the following: ≥1800MPa, ≥1810MPa, ≥1820MPa, ≥1830MPa, ≥1840MPa, ≥1850MPa, ≥1860MPa,

[0107] ≥1870MPa, ≥1880MPa, ≥1890MPa or ≥1900MPa.

[0108] In some embodiments, the elongation after fracture of the cobalt-free steel is ≥10%, further ≥11%, further ≥12%, and can also be selected from any one of the following: ≥10%, ≥10.5%, ≥11%, ≥11.5%, ≥12%, ≥12.5% ​​or ≥13%.

[0109] The applicant has found through a large number of experiments that although high-cost metals such as Co, which is traditionally used for martensite strengthening, are not used, and Ti is not introduced, the type and proportion of metal elements in the raw materials are further finely adjusted, and the structure of the precipitated phase is relatively stable. The precipitated phase in some steels has a specific equivalent radius.

[0110] In some embodiments, the cobalt-free steel includes a martensitic matrix, and a coherent NiAl phase and a semi-coherent carbide phase dispersed in the martensitic matrix.

[0111] In some embodiments, the semi-coherent carbide phase may be selected from (Mo, Cr) 2 C phase, Cr 2 One or more of C phase, NbC phase.

[0112] In some embodiments, the cobalt-free steel comprises a martensitic matrix, and a coherent NiAl phase and a semi-coherent (Mo, Cr) phase dispersed in the martensitic matrix. 2 Phase C.

[0113] In some embodiments, the cobalt-free steel comprises a martensitic matrix, and a coherent NiAl phase and a semi-coherent Cr phase dispersed in the martensitic matrix. 2 C phase, semi-coherent NbC phase.

[0114] In some embodiments, in the cobalt-free steel, the coherent NiAl phase has a B2 type structure.

[0115] The equivalent radius distribution of the coherent NiAl phase shows that with the increase of Al content, the dense equivalent radius of the NiAl precipitation phase gradually decreases and tends to be stable.

[0116] In some embodiments, in the cobalt-free steel, the equivalent radius of the coherent NiAl phase is 0.5 nm to 4 nm, further 1.0 nm to 2 nm, further 1.05 nm to 1.9 nm, and can also be selected from the following equivalent radii or an interval consisting of two equivalent radii: 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1.0 nm, 1.05 nm, 1.1 nm, 1.11 nm, 1.2 nm, 1.3 nm, 1.4 nm,

[0117] 1.5nm, 1.6nm, 1.7nm, 1.8nm, 1.82nm, 1.9nm, 2.0nm, 2.1nm, 2.2nm,

[0118] 2.3nm, 2.4nm, 2.5nm, 2.6nm, 2.7nm, 2.8nm, 2.9nm, 3.0nm, 3.1nm, 3.2nm, 3.3nm, 3.4nm, 3.5nm, 3.6nm, 3.7nm, 3.8nm, 3.9nm, 4.0nm, etc.

[0119] Controlling the volume ratio of the coherent NiAl phase in the cobalt-free steel within a suitable range is conducive to obtaining a steel with better comprehensive mechanical properties. If the ratio is higher than the suitable range, it may cause a low content of the semi-coherent precipitate phase or an uneven distribution of the coherent precipitate phase; if the ratio is lower than the suitable range, it cannot have a significant strengthening effect, resulting in insufficient material strength.

[0120] In some embodiments, in the cobalt-free steel, the volume ratio of the coherent NiAl phase in the cobalt-free steel is 4% to 10%, and can also be selected from the following volume ratios or an interval consisting of two volume ratios: 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0121] In some embodiments, in the cobalt-free steel, the number density of the coherent NiAl phase in the cobalt-free steel is 2×10 24 / m 3 ~5×10 24 / m 3 , which can be further 3×10 24 / m 3 ~5×10 24 / m 3 , and further can be 3×10 24 / m 3 ~4×10 24 / m 3 , and can also be selected from the following number density or two number density intervals: 2×10 24 / m 3 , 2.5×1024 / m 3 , 3×10 24 / m 3 , 3.5×10 24 / m 3 , 3.6×10 24 / m 3 , 4×10 24 / m 3 , 4.5×10 24 / m 3 , 5×10 24 / m 3 wait.

[0122] In some embodiments, in the cobalt-free steel, the volume ratio of the coherent NiAl phase in the cobalt-free steel is 4% to 10%, and its number density is 2×10 24 / m 3 ~5×10 24 / m 3 .

[0123] In some embodiments, in the cobalt-free steel, the volume ratio of the coherent NiAl phase in the cobalt-free steel is 4% to 10%, and its number density is 3×10 24 / m 3 ~5×10 24 / m 3 .

[0124] In some embodiments, in the cobalt-free steel, the volume ratio of the coherent NiAl phase in the cobalt-free steel is 4% to 10%, and its number density is 3×10 24 / m 3 ~4×10 24 / m 3 .

[0125] In some embodiments, in the cobalt-free steel, Mn is distributed at one end of at least a portion of the coherent NiAl phase.

[0126] In some embodiments, in the cobalt-free steel, the semi-coherent (Mo, Cr) 2 Phase C has an HCP type structure.

[0127] In some embodiments, the cobalt-free steel comprises a martensitic matrix, and a coherent NiAl phase and a semi-coherent (Mo, Cr) phase dispersed in the martensitic matrix. 2 C phase, the semi-coherent (Mo, Cr) 2 Phase C has an HCP type structure.

[0128] In some embodiments, in the cobalt-free steel, the semi-coherent (Mo, Cr)2 The equivalent radius of the C phase is 0.1nm to 2.5nm, further 1.0nm to 1.5nm, further 1.3nm to 1.46nm, and can also be selected from the following equivalent radii or an interval consisting of two equivalent radii: 0.1nm, 0.2nm, 0.3nm, 0.4nm, 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1.0nm, 1.05nm,

[0129] 1.1nm, 1.11nm, 1.2nm, 1.3nm, 1.4nm, 1.46nm, 1.5nm, 1.6nm, 1.7nm,

[0130] 1.8nm, 1.82nm, 1.9nm, 2.0nm, 2.1nm, 2.2nm, 2.3nm, 2.4nm, 2.5nm, etc.

[0131] In some embodiments, in the cobalt-free steel, at least a portion of the semi-coherent (Mo, Cr) 2 The deviation of the major axis of the C phase relative to the {100} crystal plane direction of the martensite matrix is ​​not more than 2°, further may be not more than 1.5°, and further may be not more than 1°.

[0132] In some embodiments, in the cobalt-free steel, the semi-coherent (Mo, Cr) 2 The number density of C phase in the cobalt-free steel is 4.5×10 23 / m 3 ~5.5×10 23 / m 23 , which can be further 4.6×10 23 / m 3 ~5.4×10 23 / m 23 , and further can be 4.8×10 23 / m 3 ~5.2×10 23 / m 23 , and can also be selected from the following number density or two number density intervals: 4.5×10 23 / m 3 , 4.6×10 23 / m 23 , 4.7×10 23 / m 3 , 4.8×10 23 / m 23 , 4.9×10 23 / m 3 5.0×10 23 / m 23, 5.1×10 23 / m 23 , 5.2×10 23 / m 23 , 5.3×10 23 / m 23 , 5.4×10 23 / m 23 , 5.5×10 23 / m 23 .

[0133] In some embodiments, in the cobalt-free steel, the coherent NiAl phase and the semi-coherent (Mo, Cr) 2 The number density ratio of phase C is (6.5-7.5):1, and can further be (6.6-7.4):1, and further can be (6.8-7.2):1. It can also be selected from the following number density intervals or an interval consisting of two number densities: 6.5:1, 6.5:1, 6.7:1, 6.8:1, 6.9:1, 7.0:1, 7.1:1, 7.2:1, 7.3:1, 7.4:1, 7.5:1, etc.

[0134] In some embodiments, in the cobalt-free steel, the semi-coherent (Mo, Cr) 2 The number density of C phase in the cobalt-free steel is 4.5×10 23 / m 3 ~5.5×10 23 / m 23 , the coherent NiAl phase and the semi-coherent (Mo, Cr) 2 The number density ratio of phase C is (6.5~7.5):1.

[0135] In some embodiments, in the cobalt-free steel, the semi-coherent (Mo, Cr) 2 The number density of C phase in the cobalt-free steel is 4.8×10 23 / m 3 ~5.2×10 23 / m 23 , the coherent NiAl phase and the semi-coherent (Mo, Cr) 2 The number density ratio of phase C is (6.8~7.2):1.

[0136] In some embodiments, in the cobalt-free steel, the martensitic matrix includes nano-twinned martensite.

[0137] In some embodiments, in the cobalt-free steel, the nano-twinned martensite is in the shape of long strips.

[0138] In some embodiments, in the cobalt-free steel, the average width of the nano-twinned martensite is 14 to 15 nm, and can also be selected from the following average widths: 14.0 nm, 14.1 nm, 14.2 nm, 14.3 nm, 14.4 nm, 14.5 nm, 14.6 nm, 14.7 nm, 14.8 nm, 14.9 nm, and 15.0 nm.

[0139] In some embodiments, in the cobalt-free steel, the nano-twinned martensite is in the shape of long strips, and the average width is 14-15 nm.

[0140] The applicant has found that controlling the volume ratio of martensite to austenite within a suitable range is conducive to obtaining steel with excellent mechanical properties. If the ratio is higher than the suitable range, the austenite phase may not contribute enough strength, resulting in a significant decrease in the strength of the steel; if the ratio is lower than the suitable range, the ability of austenite to coordinate deformation may be limited, thereby affecting the plasticity and toughness of the steel.

[0141] In some embodiments, in the cobalt-free steel, in the cobalt-free steel having a dual phase of martensite and austenite, the volume ratio of the martensite to the austenite is (7-20):1, further can be (7-19):1, and further can be (7-7.5):1.

[0142] In some embodiments, in the cobalt-free steel, the volume ratio of austenite in the cobalt-free steel having a dual phase of martensite and austenite is selected from 11% to 13%, and can also be selected from the following volume ratios or an interval consisting of two volume ratios: 11%, 11.5%, 12%, 12.5%, 13%, etc.

[0143] In some embodiments, in the cobalt-free steel, the austenite includes particles of 1 to 2 μm, and can also be selected from the following particle size ranges or two composition ranges: 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, etc.

[0144] In some embodiments, in the cobalt-free steel, the austenite is distributed at the high-angle grain boundaries of the martensite, and the high-angle grain boundaries refer to grain boundaries where the orientation difference between adjacent grains is greater than 15°.

[0145] The applicant has found that controlling the sum of the weight ratios of Ni and Al within an appropriate range is conducive to obtaining steel with excellent mechanical properties. If the sum of the weight ratios of Ni and Al is higher than the appropriate range, the NiAl precipitate phase fraction may grow slowly after reaching a high value, and the high Al content may have a great impact on the plasticity and toughness of the steel, thereby reducing the optimal mechanical properties of the steel; if the sum of the weight ratios of Ni and Al is lower than the appropriate range, the proportion of the NiAl precipitate phase may be low, and sufficient strength contribution may not be provided.

[0146] In some embodiments, in the cobalt-free steel, the total weight percentage of Ni element and Al element is 8.5% to 22%, and can also be selected from the following weight percentage or the interval consisting of two weight percentages: 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, etc.

[0147] In some embodiments, in the cobalt-free steel, the weight ratio of Ni element to Al element is (3-9):1, and can also be selected from the following particle size or two composition ranges: 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1.

[0148] The applicant has found that controlling the sum of the weight ratios of Mo and Cr within an appropriate range is conducive to obtaining steel with excellent mechanical properties. If the sum of the weight ratios of Mo and Cr is higher than the appropriate range, it may lead to semi-coherent (Mo, Cr) 2 If the amount of C phase precipitation is too large, dislocation pile-up will occur prematurely, resulting in premature crack initiation and brittle fracture. If the sum of the weight proportions of Mo and Cr is lower than the appropriate range, it may not be possible to form a sufficient number of NiAl phases and Mo clusters, affecting the strength and plasticity of the steel.

[0149] In some embodiments, in the cobalt-free steel, the total weight percentage of the Mo element and the Cr element is 2% to 7%, and can also be selected from the following weight percentages or an interval consisting of two weight percentages: 2%, 3%, 4%, 5%, 6%, 7%, etc.

[0150] In some embodiments, in the cobalt-free steel, the weight ratio of Mo element to Cr element is (0.05-1.5):1, and can also be selected from the following weight ratios or two weight ratios: 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc.

[0151] In some embodiments, in the cobalt-free steel, the weight ratio of the Mo element, the Cr element and the C element satisfies (Mo+Cr) / C=10-30, further can be 15-25, and further can be 18-22.

[0152] In some embodiments, the cobalt-free steel comprises, by mass percentage, 1% to 9% Cr, 12% to 17% Ni, 1% to 5% Al, 1% to 2% Mo, 0% to 1.75% Mn, 0% to 0.15% Nb, 0.05% to 0.2% C, and the balance Fe.

[0153] In some embodiments, the cobalt-free steel comprises, by mass percentage, 2.5-9% Cr, 12-14% Ni, 1-3% Al, 1-1.5% Mo, 0-1.5% Mn, 0-0.1% Nb, 0.08-0.2% C, and the balance Fe.

[0154] In some embodiments, the cobalt-free steel comprises, by mass percentage, 2.5-9% Cr, 12-14% Ni, 1-3% Al, 1-1.5% Mo, 0.5-1.5% Mn, 0.08-0.2% C, and the balance Fe.

[0155] In some embodiments, the cobalt-free steel comprises, by mass percentage, 2.5-9% Cr, 12-14% Ni, 1-3% Al, 1-1.5% Mo, 0.05-0.1% Nb, 0.08-0.2% C, and the balance Fe.

[0156] In some embodiments, the cobalt-free steel further includes unavoidable impurities introduced due to raw material purity or during the preparation process.

[0157] In some embodiments, the impurities include the following S, P, O, and N, wherein S≤10ppm, P≤15ppm, O≤10ppm, N≤10ppm, and the total impurity content is ≤50ppm.

[0158] In some embodiments, the cobalt-free steel comprises, by mass percentage, 1% to 9% Cr, 12% to 17% Ni, 1% to 5% Al, 1% to 2% Mo, 0% to 1.75% Mn, 0% to 0.15% Nb, 0.05% to 0.2% C, and the remainder Fe and unavoidable impurities.

[0159] In some embodiments, the cobalt-free steel comprises, by mass percentage, various elements as follows:

[0160] 2.5-9% Cr, 12-14% Ni, 1-3% Al, 1-1.5% Mo, 0-1.5% Mn, 0-0.1% Nb, 0.08-0.2% C, the balance Fe and inevitable impurities.

[0161] In some embodiments, the cobalt-free steel comprises, by mass percentage, various elements as follows:

[0162] 2.5-9% Cr, 12-14% Ni, 1-3% Al, 1-1.5% Mo, 0.5-1.5% Mn, 0.08-0.2% C, the balance Fe and inevitable impurities.

[0163] In some embodiments, the cobalt-free steel comprises, by mass percentage, 2.5-9% Cr, 12-14% Ni, 1-3% Al, 1-1.5% Mo, 0.05-0.1% Nb, 0.08-0.2% C, and the remainder Fe and unavoidable impurities.

[0164] The second aspect of the present application provides a method for preparing cobalt-free steel, which can prepare the cobalt-free steel described in the first aspect.

[0165] In some embodiments, the preparation method comprises the following steps:

[0166] S100: smelting the raw materials to form ingots; wherein the raw materials are mixed according to element ratios;

[0167] S200: homogenizing the ingot and water cooling it;

[0168] S300: cold rolling the ingot after homogenization treatment and water cooling to obtain a cold-rolled material;

[0169] S400: performing a solution treatment, water cooling, and liquid nitrogen deep cooling on the cold-rolled material to obtain a steel material having martensite and austenite;

[0170] S500: performing aging treatment on the steel material having martensite and austenite to obtain the cobalt-free steel.

[0171] In some embodiments, the preparation method comprises the following steps:

[0172] S100: smelting the raw materials to form ingots; wherein the raw materials are mixed according to element ratios;

[0173] S200: homogenizing the ingot at a suitable temperature, and water cooling the ingot to a suitable temperature;

[0174] S300: cold rolling the ingot after homogenization treatment and water cooling to obtain a cold-rolled material;

[0175] S400: performing a solution treatment on the cold-rolled material at a suitable temperature, water cooling to a suitable temperature, and deep cooling with liquid nitrogen to obtain a steel material having martensite and austenite;

[0176] S500: performing aging treatment on the steel material having martensite and austenite at a suitable temperature to obtain the cobalt-free steel.

[0177] In some embodiments, the preparation method comprises the following steps:

[0178] S100: smelting the raw materials to form ingots; wherein the raw materials are mixed according to element ratios;

[0179] S200: homogenizing the ingot at 1150-1250° C. and water cooling the ingot to 20-35° C.;

[0180] S300: cold rolling the ingot after homogenization treatment and water cooling to obtain a cold-rolled material;

[0181] S400: subjecting the cold-rolled material to a solution treatment at 900-1000° C., water cooling to 20-35° C., and deep cooling with liquid nitrogen to obtain a steel material having martensite and austenite;

[0182] S500: performing aging treatment on the steel material having martensite and austenite at 500-600° C. to obtain the cobalt-free steel.

[0183] In some embodiments, the raw materials are mixed according to the element ratio of the cobalt-free steel described in the first aspect.

[0184] The preparation method firstly vacuum melts the raw materials and homogenizes the ingots, then water cools them to room temperature and then cold rolls them to obtain steel plates, then solid solution treats the steel plates and water cools and deep freezes them with liquid nitrogen to eliminate unstable austenite, and finally performs aging treatment at an appropriate temperature to obtain cobalt-free steel. The preparation method is relatively simple and easy to mass produce, and the obtained steel has good plasticity and work hardening ability.

[0185] In some embodiments, the smelting process is performed in a vacuum induction furnace, a vacuum resistance furnace or a vacuum non-consumable furnace.

[0186] Homogenization treatment is beneficial to eliminate segregation during the smelting process. If the homogenization treatment time is too short, the purpose of eliminating segregation may not be achieved, and the carbide may not be well dissolved; if the homogenization treatment time is too long, it may lead to high energy consumption in the processing process. In some embodiments, in the preparation method, the ingot is homogenized at 1150-1250°C, and can further be 1180-1220°C, and can also be selected from one or two of the following temperature intervals: 1150°C, 1160°C, 1170°C, 1180°C, 1190°C, 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, etc.

[0187] In some embodiments, in the preparation method, the homogenization treatment time is 1 to 3 hours, and can further be 2 to 3 hours.

[0188] In some embodiments, in the preparation method, the ingot is homogenized at 1150-1250° C. for 1-3 hours.

[0189] In some embodiments, in the preparation method, the total reduction of the cold-rolled material obtained by cold rolling is 30% to 70%, and can further be 30% to 50%.

[0190] Solution treatment is conducive to uniform chemical composition, eliminating work hardening, and facilitating cold processing in subsequent processes. If the solution treatment time is too short, the composition may not be uniform, which may lead to rolling cracks in the subsequent cold rolling process; if the solution treatment time is too long, it may cause excessive grain growth, which is harmful to the toughness and plasticity of the steel.

[0191] In some embodiments, in the preparation method, the cold-rolled material is solution treated at 900-1000° C. and water-cooled to 20-35° C. to obtain supersaturated martensite; the supersaturated martensite is deep-cooled with liquid nitrogen to eliminate unstable austenite, thereby obtaining the steel having martensite and austenite.

[0192] In some embodiments, in the preparation method, the cold-rolled material is solution treated at 900-1000°C, and further at 900-950°C.

[0193] In some embodiments, in the preparation method, the solution treatment time of the cold-rolled material is 5 to 60 minutes, and can further be 30 to 60 minutes.

[0194] In some embodiments, in the preparation method, the cold-rolled material is solution treated at 900-1000° C. for 5-60 minutes.

[0195] During the quenching process, austenite transforms into martensite, but the residual austenite in the water cooling process alone is unstable due to insufficient supercooling. The present application performs appropriate cryogenic treatment on the steel after water cooling to improve the stability of the residual austenite. It is speculated that the TRIP effect may continue to occur at high stress levels, passivating microcracks and reducing the stress concentration at the crack front, thereby greatly improving the plastic toughness and work hardening ability of the test steel.

[0196] When the aging temperature is higher than the appropriate range, the supersaturation of the intermetallic compounds is low and the second phase is significantly coarsened; while when the aging temperature is lower than the appropriate range, the precipitation of nano-intermetallic compounds is insufficient.

[0197] Too long an aging treatment may cause the precipitate to grow, which is not conducive to the formation of a coherent precipitate. Too short an aging treatment may cause the precipitate to be insufficient in size and insufficient in number to contribute to sufficient strength.

[0198] In some embodiments, in the preparation method, the aging treatment time of the steel having martensite and austenite at 500-600° C. is 60-720 min, further 120-600 min, and further 240-360 min.

[0199] A third aspect of the present application provides a stainless steel product, which is made of the cobalt-free steel described in the first aspect or the cobalt-free steel prepared by the preparation method described in the second aspect.

[0200] This stainless steel product has high yield strength and excellent fracture toughness, and can be used in fields such as transportation, aerospace, etc. that have higher requirements on the comprehensive performance of steel.

[0201] The fourth aspect of the present application provides a cobalt-free steel as described in the first aspect or a cobalt-free steel prepared by the preparation method as described in the second aspect as an ultra-high-strength steel, or in the preparation of aircraft landing gear, rocket engine casing, high-strength bolts for high-pressure vessels or applications.

[0202] This cobalt-free steel has good comprehensive mechanical properties and better service safety compared to traditional steel.

[0203] In order to make it easier to understand and implement the present application, the following easier-to-implement, more specific and detailed embodiments and comparative examples are provided as references.

[0204] Unless otherwise specified, the raw materials used in the following experiments can be purchased from the market.

[0205] The following examples are not particularly limited, and the instrument models involved are:

[0206] Test method:

[0207] Steel processing methods:

[0208] The experimental steel was processed into plate-shaped tensile specimens with a parallel section of 20 mm and a cross section of 1.5 mm × 4 mm by wire cutting. The strain rate was 2 × 10 -3 / s, and the microstructure and fracture of the steel were characterized and analyzed using a SUPRA55 scanning electron microscope, a Technai F30 transmission electron microscope, and a LEAP-5000XR three-dimensional atom probe.

[0209] Strength and plasticity test and calculation method: CMT4105 universal tensile testing machine was used to test the tensile properties at room temperature, with a strain rate of 10 -3 s -1 The performance of the plate-shaped tensile specimens polished with sandpaper was tested and the stress-strain curves during the experiment were recorded to obtain data such as yield strength, tensile strength, and elongation after fracture.

[0210] Equivalent radius: For a certain particle, the radius corresponding to a sphere of the same mass is recorded as its equivalent radius. For a particle mixture, unless otherwise specified, the equivalent radius of the particle refers to the average value. The test method is: mechanical polishing and etching methods are used for production, SEM and EBSD are used for characterization, and Nano Measure or Channel 5 is used for subsequent processing to obtain the average particle size and distribution of austenite.

[0211] Twinned martensite: It is mainly formed in steel with a high carbon content. Because its fine (sub)structure is a large number of twins, it is also called twinned martensite. This twin disappears near the boundary of the martensite sheet and does not pass through the martensite boundary. The substructure on the boundary is a complex dislocation network.

[0212] Calculation method of the volume ratio of martensite to austenite (or volume fraction of austenite): First, a sample is prepared by mechanical polishing / electrolytic polishing and characterized by SEM and EBSD to obtain the volume ratio of martensite to austenite.

[0213] Precipitation phase (coherent precipitation phase NiAl, semi-coherent precipitation phase Cr 2 C.Mo 2 C) Average radius test and calculation method: Technai F30 transmission electron microscope and LEAP-5000XR three-dimensional atom probe were used to characterize and analyze the precipitated phase after aging.

[0214] Table 1 Steel alloy composition (wt.%)

[0215] element Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Mn 1.5 / / 3 / Nb / 0.1 / / / Cr 2.5 9 / / / Ni 14 12 14 8 20 Al 2 2 3 1 3 Mo 1.5 1 5 / 5 C 0.2 0.08 / / / Fe Bal. Bal. Bal. Bal. Bal.

[0216] Example 1

[0217] Select high-purity (>99.95%) raw materials, weigh the raw materials as shown in Table 1, and smelt the raw materials (vacuum non-consumable furnace, smelting 6 times) to make ingots (10mm×10mm×60mm);

[0218] The ingot is homogenized at 1200° C. (treatment time 2 h), and water-cooled to 20-35° C.;

[0219] The ingot after homogenization treatment and water cooling is cold rolled to obtain a cold rolled material (cold rolled 30%);

[0220] The cold-rolled material is subjected to a solution treatment at 900° C. (treatment time 1 h), water-cooled to 20-35° C., and deep-cooled with liquid nitrogen (treatment time 4 h) to obtain a steel material having martensite and austenite;

[0221] The steel material having martensite and austenite is subjected to aging treatment at 500° C. (treatment time 4 h) to obtain the cobalt-free steel T1.

[0222] The cobalt-free steel T1 of Example 1 has a yield strength of 1730 MPa, a tensile strength of 2105 MPa, an elongation after fracture of 12.1%, a uniform elongation of up to 7.3%, a yield strength ratio of 0.82, and has excellent strength-plasticity matching.

[0223] The same performance test method as in Example 1 was used for the two commercial products. The test results are as follows: Figure 1 As shown, compared with C300 (uniform elongation 1.2%) and Aemet100 (uniform elongation 2.8%), the uniform elongation of T1 can reach 7.3%, indicating that T1 has better ability to resist plastic instability and service safety.

[0224] The fracture of the cobalt-free steel T1 tensile specimen of Example 1 is as follows: Figure 2As shown in the figure, the fracture is mainly microporous aggregation type, the dimple size is basically below 2μm, accompanied by a small amount of cleavage fracture, and the secondary cracks are mainly formed at the martensite-austenite phase interface. EBSD is used to analyze the phase distribution of T1, as shown in the figure. Figure 3 As shown in Figure 1, after cryogenic treatment with liquid nitrogen, the content of retained austenite (face-centered cubic, FCC) is about 12.5%, mainly distributed at the high-angle interface of martensite. The low-magnification and high-magnification patterns and TEM diffraction results of T1 steel after water cooling and cryogenic treatment with liquid nitrogen are shown in Figure 1. Figure 4 As shown in the figure, long strip-shaped nanotwins with an average width of 14.7 nm are formed, that is, T1 forms dense twin boundaries during the quenching process, which is beneficial to greatly reduce the mean free path of dislocations, improve the dislocation storage capacity, and significantly improve the plasticity and work hardening ability of T1.

[0225] The precipitated phase of T1 was characterized by transmission electron microscopy, three-dimensional atom probe and 3D-APT, such as Figure 5 and Figure 6 shown. Figure 7 The composition distribution diagrams of all isoconcentration surfaces of coherent and semi-coherent precipitates are given. The precipitates include spherical NiAl phases and long strips of M 2 C (Mo, Cr) carbides, B2-NiAl and body-centered cubic (BCC) martensitic matrix maintain good coherence and extremely low mismatch. NiAl is evenly dispersed in the martensitic matrix with an average radius of 1.08±0.03nm and a number density of up to 3.6×10 24 / m 3 . M 2 C carbides have an HCP structure and have an obvious orientation relationship with the martensite matrix. The long axis is consistent with the (100) direction of the matrix, the equivalent radius is 1.38±0.08nm, and the number density reaches 5.0×10 23 / m 3 In addition, Mn tends to be distributed at one end of NiAl; C, Cr, and Mo elements have low solid solubility in NiAl and are excluded from the interface between NiAl and the matrix. This shows that Mn is conducive to the precipitation nucleation of NiAl precipitation phase, and C, Cr, and Mo can also precipitate to form M 2 C carbide.

[0226] Example 2

[0227] The preparation method of Example 2 is substantially the same as that of Example 1, except that the Cr content is greatly increased, the Mn element is not introduced, and on this basis, 0.1% Nb is added and the C element is reduced to 0.08%.

[0228] The same test method as in Example 1 was used to measure the corresponding mechanical properties of the ultra-high strength steel in Example 2. Figure 8The tensile strength is 1920MPa, the yield strength is 1697MPa, the elongation after fracture is 10.4%, and the yield strength ratio is 0.88.

[0229] Compared with Example 1, the strengthening mechanism of Example 2 has not changed much, and it is still the synergistic strengthening of coherent and semi-coherent precipitation. The content of Ni and Al elements remains basically unchanged, the equivalent radius of the coherent precipitation strengthening phase NiAl is 1.86±0.04nm, and the density has not changed much, while the type of semi-coherent precipitation strengthening phase has changed slightly, from Mo 2 C.Cr 2 C is transformed into NbC (equivalent radius is 20-30nm) and Cr 23 C 6 (The equivalent radius is 100-200 nm). Its strength and plasticity are slightly lower than those of Example 1, but it also maintains a good match between strength and plasticity.

[0230] Comparative Example 1:

[0231] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that:

[0232] The Al content was increased to 3wt.%, Cr, Mn and C elements were removed, and the Mo content was increased to 5wt.%.

[0233] The same test method as in Example 1 was used to measure the corresponding mechanical properties of the ultra-high strength steel in Comparative Example 1. Fig.10 The tensile strength is 1851MPa, the yield strength is 1649MPa, the elongation after fracture is 3.5%, the yield strength ratio is 0.89, and the uniform elongation is 2.7%.

[0234] Comparative Example 1 removes elements such as Cr, Mn, and C, but increases the content of alloying elements such as Mo and Al, and reduces the Ni / Al ratio. The radius of the NiAl precipitation phase obtained is 2.09±0.10nm. Compared with Example 1, the strength of Comparative Example 1 decreases significantly, and the plasticity also decreases significantly, with the elongation after fracture decreasing from 12.1% to 3.5%. Excessive content of Al elements and a low Ni / Al ratio will lead to a significant decrease in the plasticity of the steel.

[0235] Comparative Example 2:

[0236] The preparation method of Comparative Example 2 is substantially the same as that of Example 1, except that:

[0237] The Mn content was increased to 3wt.%, the Al content was reduced to 1wt.%, the Ni content was reduced to 6wt.%, and the Mo, C and Cr content were reduced to 0wt.%.

[0238] The same test method as in Example 1 was used to measure the corresponding mechanical properties of the ultra-high strength steel in Comparative Example 1. Fig.11 The tensile strength is 1141 MPa, the yield strength is 1120 MPa, the elongation after fracture is 8.3%, the yield strength ratio is 0.98, the uniform elongation is 3.0%, and the radius of the obtained NiAl precipitation phase is 1.89±0.08 nm.

[0239] Comparative Example 2 greatly reduces the content of Ni and Al, thereby reducing the density of the NiAl precipitation phase, resulting in a significant reduction in its strength. It can be seen that NiAl coherent precipitation strengthening has a great contribution to the relative strength.

[0240] Comparative Example 3

[0241] The preparation method of Comparative Example 3 is substantially the same as that of Example 1, except that the Cr, Mn and C elements are removed, the Ni content is increased to 20 wt.%, the Mo content is increased to 5%, and the Al content is increased to 3 wt.%.

[0242] The same test method as in Example 1 was used to measure the corresponding mechanical properties of the ultra-high strength steel in Example 3. Fig. 9 The tensile strength is 2019 MPa, the yield strength is 1777 MPa, the elongation after fracture is 8.4%, the yield strength ratio is 0.88, the uniform elongation is 4.5%, and the radius of the obtained NiAl precipitation phase is 2.1±0.16 nm.

[0243] Comparative Example 3 removes elements such as Cr, Mn, and C, but greatly increases the content of alloying elements such as Mo and Ni. Comparative Example 3 abandons the semi-coherent precipitation strengthening phase of carbides. Although the density of the NiAl precipitation phase is increased by increasing the content of Ni and Al, it still leads to a decrease in strength and plasticity.

[0244] Figure 1 , (a), (b), and (c) are the engineering stress-strain curve, true stress-strain and work hardening rate curve of the steel in Example 1, respectively, compared with the tensile strength (UTS), yield strength (YS), total elongation (TE), and uniform elongation (UE) of traditional ultra-high strength steel Aermet100 and MaragingC300.

[0245] Figure 2 , (a) and (b) are the overall and local magnifications of the fracture surface of the test steel tensile specimen, respectively.

[0246] Figure 3 , Example 1 EBSD phase distribution; wherein the test step length is 0.05μm.

[0247] Figure 4, (a), (b) and (c) are the low-magnification TEM, high-magnification TEM and diffraction spots (SAED) of twinned martensite, respectively.

[0248] Figure 5 , (a)~(c) are the dark field images, high resolution (HRTEM) and FFT images of NiAl phase, respectively, and (d)~(f) are the dark field images, high resolution (HRTEM) and FFT images of M2C phase, respectively.

[0249] Figure 6 , (a), (b) and (c) are the isoconcentration surface distributions of 30at.% NiAl and 10at.% CrMoC, the isoconcentration surface distributions of 30at.% NiAl and 4at.% Mn with a thickness of 3nm, and the isoconcentration surface distributions of 30at.% NiAl and 10at.% CrMoC with a thickness of 3nm, respectively. (d) and (e) are the size distribution diagrams of NiAl phase and M2C phase, respectively.

[0250] Figure 7 , (a) and (b) are the composition distribution diagrams of all isoconcentration surfaces of 30at.%NiAl and 10at.%CrMoC, respectively.

[0251] Figure 8 , engineering stress-strain curve of Example 2.

[0252] Fig. 9 , engineering stress-strain curve of Example 3.

[0253] Fig.10 , engineering stress-strain curve of comparative example 1.

[0254] Fig.11 , engineering stress-strain curve of comparative example 2.

[0255] Fig.12 , a method for preparing cobalt-free steel in one embodiment of the present application.

[0256] Table 2. Room temperature tensile mechanical properties of steel

[0257]

[0258] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0259] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.

Claims

1. A cobalt-free steel, characterized in that: According to mass percentage, it contains: 1%~10% Cr, 10.5%~17% Ni, 0.5%~5% Al, 0.25%~2% Mo and 0.01%~0.2% C, 1%~2% Mn or 0.05%~0.2% Nb, and the balance Fe; The cobalt-free steel has two phase structures, martensite and austenite; the austenite is distributed at the high-angle grain boundaries of the martensite, and the high-angle grain boundaries refer to grain boundaries where the orientation difference between adjacent grains is greater than 15°; The cobalt-free steel comprises a martensitic matrix and a coherent NiAl phase and a semi-coherent carbide phase dispersed in the martensitic matrix; when the cobalt-free steel contains 1% to 2% of Mn, Mn is distributed at one end of at least a portion of the coherent NiAl phase; In the cobalt-free steel having a dual phase of martensite and austenite, the volume ratio of the martensite to the austenite is (7-20):1; the volume ratio of the austenite in the cobalt-free steel having a dual phase of martensite and austenite is selected from 11% to 13%.

2. The cobalt-free steel according to claim 1, characterized in that According to mass percentage, it contains: 1%~10% Cr, 10.5%~17% Ni, 0.5%~5% Al, 0.25%~2% Mo, 1%~2% Mn, 0.01%~0.2% C, and the balance Fe; The cobalt-free steel comprises a martensitic matrix and a coherent NiAl phase and a semi-coherent (Mo, Cr) 2 C phase dispersed in the martensitic matrix.

3. The cobalt-free steel according to claim 1, characterized in that: Satisfy at least one of the following characteristics: The coherent NiAl phase has a B2 type structure; The equivalent radius of the coherent NiAl phase is 0.5-4 nm; The volume ratio of the coherent NiAl phase in the cobalt-free steel is 4% to 10%; The number density of the coherent NiAl phase in the cobalt-free steel is 2×10 24 / m 3 ~ 5×10 24 / m 3 .

4. The cobalt-free steel according to claim 3, characterized in that: The semi-coherent carbide phase includes a (Mo, Cr)2C phase, and the cobalt-free steel satisfies at least one of the following characteristics: The semi-coherent (Mo, Cr)2C phase has an HCP type structure; The equivalent radius of the semi-coherent (Mo,Cr)2C phase is 0.1-2.5nm; The deviation of the major axis of at least a portion of the semi-coherent (Mo,Cr)2C phase relative to the {100} crystal plane direction of the martensitic matrix does not exceed 2°; The number density of the semi-coherent (Mo,Cr)2C phase in the cobalt-free steel is 4.5×10 23 / m 3 ~ 5.5×10 23 / m 23 ; The number density ratio of the coherent NiAl phase to the semi-coherent (Mo,Cr)2C phase is (6.5~7.5):

1.

5. The cobalt-free steel according to any one of claims 1 to 4, characterized in that The martensitic matrix includes nano-twinned martensite; the nano-twinned martensite is in the shape of long strips, and the average width is 14-15 nm.

6. The cobalt-free steel according to any one of claims 1 to 4, characterized in that Satisfy at least one of the following characteristics: In the cobalt-free steel having a dual phase of martensite and austenite, the volume ratio of the martensite to the austenite is (7-7.5):1; The volume ratio of the austenite in the cobalt-free steel having a martensite-austenite dual phase is selected from 11.5% to 12.5%; The austenite includes particles of 1 to 2 μm.

7. The cobalt-free steel according to claim 6, characterized in that: Satisfy at least one of the following characteristics: In the cobalt-free steel, the total weight proportion of Ni element and Al element is 8.5% to 22%; In the cobalt-free steel, the weight ratio of Ni element to Al element is (3-9):

1.

8. The cobalt-free steel according to any one of claims 1 to 3, characterized in that: Satisfy at least one of the following characteristics: In the cobalt-free steel, the total weight proportion of Mo element and Cr element is 2% to 7%; In the cobalt-free steel, the weight ratio of Mo element to Cr element is (0.05~1.5):

1.

9. The cobalt-free steel according to claim 1, characterized in that: According to mass percentage, it contains: 2.5%~9% Cr, 12%~14% Ni, 1%~3% Al, 1%~1.5% Mo, 1%~1.5% Mn, 0.08%~0.2% C, and the balance Fe and unavoidable impurities; or In terms of mass percentage, it contains: 2.5%~9% Cr, 12%~14% Ni, 1%~3% Al, 1%~1.5% Mo, 0.05%~0.1% Nb, 0.08%~0.2% C, and the remainder Fe and inevitable impurities.

10. A method for preparing cobalt-free steel, characterized in that: The following steps are involved: The raw materials are smelted to form ingots; wherein the raw materials are mixed according to the element ratio of the cobalt-free steel according to claim 1, 2 or 9; The ingot is homogenized at 1150-1250° C. and water-cooled to 20-35° C.; cold rolling the homogenized and water-cooled ingot to obtain a cold-rolled material; The cold-rolled material is subjected to a solution treatment at 900-1000° C., water-cooled to 20-35° C., and deep-cooled with liquid nitrogen to obtain a steel material having martensite and austenite; The steel material having martensite and austenite is subjected to aging treatment at 500-600° C. to obtain the cobalt-free steel.

11. The preparation method according to claim 10, characterized in that: Satisfy at least one of the following characteristics: The ingot is homogenized at 1150-1250° C. for 1-3 hours; The total reduction of the cold-rolled material obtained by cold rolling is 30% to 70%; The cold-rolled material is subjected to a solution treatment at 900-1000° C., and water-cooled to 20-35° C. to obtain supersaturated martensite; the supersaturated martensite is subjected to liquid nitrogen deep cooling to eliminate unstable austenite, and the steel having martensite and austenite is obtained; the cold-rolled material is subjected to a solution treatment at 900-1000° C. for 5-60 minutes; The steel material having martensite and austenite is subjected to aging treatment at 500-600° C. for 60-720 minutes.

12. A stainless steel product, characterized in that: The invention is made of the cobalt-free steel according to any one of claims 1 to 9 or the cobalt-free steel prepared by the preparation method according to any one of claims 10 to 11.

13. Use of the cobalt-free steel according to any one of claims 1 to 9 or the cobalt-free steel prepared by the preparation method according to any one of claims 10 to 11 in the preparation of aircraft landing gear, rocket engine casing, high-pressure container or high-strength bolt.

Citation Information

Patent Citations

  • Aluminum-strengthened maraging steel and preparing method thereof

    CN105568151A

  • B2 nanoparticle coherent precipitation-hardened ultrahigh-strength maraging stainless steel and preparation method thereof

    CN111593260A

  • Maraging stainless steel heat treatment method

    CN113981187A

  • Cobalt-free maraging steel with double-phase structure and preparation method of cobalt-free maraging steel

    CN114622145A

  • Valve

    US4754950A